Hypothermia in mouse is caused by adenosine A1 and A3 receptor agonists and AMP via three distinct mechanisms. (1st March 2017) - Carlin, Jesse Lea; Jain, Shalini; Gizewski, Elizabeth; Wan, Tina C.; Tosh, Dilip K.; Xiao, Cuiying; Auchampach, John A.; Jacobson, Kenneth A.; Gavrilova, Oksana; Reitman, Marc L.
Abstract: Small mammals have the ability to enter torpor, a hypothermic, hypometabolic state, allowing impressive energy conservation. Administration of adenosine or adenosine 5'-monophosphate (AMP) can trigger a hypothermic, torpor-like state. We investigated the mechanisms for hypothermia using telemetric monitoring of body temperature in wild type and receptor knock out ( Adora1 −/−, Adora3 −/− ) mice. Confirming prior data, stimulation of the A3 adenosine receptor (AR) induced hypothermia via peripheral mast cell degranulation, histamine release, and activation of central histamine H1 receptors. In contrast, A1 AR agonists and AMP both acted centrally to cause hypothermia. Commonly used, selective A1 AR agonists, including N 6 -cyclopentyladenosine (CPA), N 6 -cyclohexyladenosine (CHA), and MRS5474, caused hypothermia via both A1 AR and A3 AR when given intraperitoneally. Intracerebroventricular dosing, low peripheral doses of Cl-ENBA [(±)-5'-chloro-5'-deoxy- N 6 - endo -norbornyladenosine], or using Adora3 −/− mice allowed selective stimulation of A1 AR. AMP-stimulated hypothermia can occur independently of A1 AR, A3 AR, and mast cells. A1 AR and A3 AR agonists and AMP cause regulated hypothermia that was characterized by a drop in total energy expenditure, physical inactivity, and preference for cooler environmental temperatures, indicating a reduced body temperature set point. Neither A1 AR nor A3 AR was required for fasting-induced torpor. A1 AR and A3 AR agonists and AMP trigger regulated hypothermia via three distinct mechanisms. Graphical abstract: Highlights: Some commonly used A1 AR agonists are not selective; they act at A3 AR. A1 AR, A3 AR, and AMP are three distinct adenosine-related inducers of hypothermia. Neither A1 AR nor A3 AR is required for fasting-induced torpor. AMP can cause hypothermia via the brain, independent of A1 AR and A3 AR.